A Critical Discourse Analysis of the Construction of Acehnese-Chinese Ethnic Identity in Socio-Political Dynamics - Riyani, Mufti; Mulianingsih, Ferani; Rahman, Aulia (Universitas Negeri Semarang, 2025)
This study explores how ethnic identities of Acehnese and Chinese communities are constructed through digital discourse, focusing on narratives of prejudice and integration as expressed on Facebook. Using Fairclough’s Critical Discourse Analysis (CDA) as the main framework, complemented by Van Dijk’s socio-cognitive approach and Foucault’s discourse-power relationship, this study examines how language, ideology, and social memory shape interethnic representations. Data were collected from public Facebook posts between January and September 2024 using keywords such as “Aceh and Chinese” and “Chinese and Aceh,” and supported by interviews with selected users. The findings reveal a pattern of dualistic representation: historical tensions and symbolic prejudices persist, while efforts towards coexistence and shared identity also emerge. The dominant narratives often come from the Acehnese community, with the Chinese group showing a more cautious approach in digital expression. Labeling, metaphor, polarization, and references to historical trauma and moments of integration are key linguistic strategies identified in the discourse. Social media platforms like Facebook play a paradoxical role—both reinforcing ethnic bias through algorithmic echo chambers and enabling counter-narratives that foster intercultural understanding. Identity construction is shaped by both internal factors (such as education and ideology) and external factors (such as collective memory, interethnic experiences, and digital infrastructure). This study highlights the importance of critical media literacy in multicultural societies, especially in post-conflict areas like Aceh. It suggests the use of inclusive digital spaces and educational interventions that promote reflective historical awareness, reduce prejudice, and support cultural integration in online and offline environments.